Avoiding lamentation: to build a future Internet. Issue 3 (2nd September 2017) - Sullivan, Andrew
ABSTRACT: The logic of growth of the Internet, both in its applications and in the evolution of its infrastructure, appears to be gradually eroding the things that made the Internet what it was in the first place. This leads one to question not what the future of the Internet will be like, but rather whether there will be one at all. The paper considers the ways important applications on the Internet affect experience of the Internet and also devices and systems that are being deployed to the Internet that might affect the network. It concludes that acceptance of the logic of Internet evolution combined with a renewed attention to end-to-end arguments may be able to protect the Internet from the damage that will otherwise occur.